Silica geothermometry and multi indices approach to characterize groundwater from Midyan region in Northwestern Saudi Arabia. (August 2022) - Zaidi, Faisal K.; Lashin, Aref; Aboud, Essam; Al Arifi, Nassir; Al-Bassam, Abdulaziz; Al-Homadhi, Emad; Anbar, Mohamed Abu
Abstract: This research was performed in the northwestern part of Saudi Arabia, where physico-chemical parameters obtained from 81 groundwater samples were interpreted. High heat flow granites underlie the study area, and their weathering and erosion cause the accumulation of radioactive elements in sediments surrounding these granites, resulting in a high temperature of the circulating water. The chalcedony (no steam loss) temperature of the circulating groundwater was determined using the dissolved silica values in the samples. Based on the obtained chalcedony temperature, the samples were categorized into two groups. The first group contained 63 samples with chalcedony temperatures less than 50 °C, and the second group contained 18 samples with temperatures above 50 °C. The Cl–SO4 –HCO3 ternary diagram showed that the samples with higher temperatures were chloride type and plotted close to the mature water. The silica concentration showed a strong correlation with chloride, indicating that Cl was mostly obtained from mineral dissolution, although the wide variation in Cl and TDS for a narrow range of silica values indicated groundwater mixing or anthropogenic influence. According to the Piper plot, the (Ca + Mg)-(SO4 +Cl), (Ca + Mg)-(HCO3 +CO3 ), and (Na + K)–(SO4 –Cl) types are the three key groundwater facies in the area. The TDS levels in water with chalcedony temperatures above 50 °C were high (over 5000 mg/L), with chloride dominating the composition. Pollution indices of the samples in terms of heavy metals and major ions were also calculated to determine the suitability of the groundwater for human consumption. The heavy metal pollution index, heavy metal evaluation index, and heavy metal contamination index indicated no HM pollution. However, the water quality index, which uses major ions to determine drinking water quality, showed that approximately 50% of the examined samples were unfit for consumption without any primary treatment. Highlights: Use of silica thermometry to determine the temperature of circulating groundwater. Water with higher temperatures are rich in Chloride and TDS. Higher temperature water belongs mainly to the Na–Cl hydrochemical facies. Groundwater in the study area is free from heavy metal pollution.